Agency, Criminogenic Risk and Needs, and Recidivism: A Prospective Longitudinal Study Including 14,000 Adult Justice-involved Individuals - Lussier, Patrick (International journal of offender therapy and comparative criminology, 2025)
Plain language summaryExamining whether justice-involved individuals can overcome criminogenic risk and needs through agency and the motivation to change their life courseWhy was the study done? A significant proportion of justice-involved individuals return in the criminal justice for a new criminal offense. Several approaches have been proposed to break this cycle. Among those, correctional services have relied on the risk-need-responsivity which stresses the importance of targeting criminogenic risk and needs through treatment and intervention. The role and importance of agency—the motivation to change their life course—as a key component of change and desistance from crime, has been neglected. What did the researchers do? The research team examined how important agency is by examining the community reentry of 14,000 justice-involved individuals and criminal recidivism over a maximum of an 8-year period. What did the researchers find? The research shows that, as expected, justice-involved individuals with more criminogenic risk and needs were more likely to recidivate. Individuals with very high risk and needs were 13 times more likely to recidivate than the very low risk and needs group. The findings did show that individuals who recognized their personal issues and were motivated to change were less likely to recidivate, especially among the higher risk and needs group. What do the findings mean? The findings reiterate that while agency is not sufficient for justice-involved individuals to change and desist from crime, it is part of the process. Addressing criminogenic risk and needs, especially for individuals facing challenging life adversities, can make desistance a long and difficult process, especially if interventions do not support agentic decisions and behaviors.